2014
DOI: 10.1590/s0034-759020140407
|View full text |Cite
|
Sign up to set email alerts
|

Compartilhando Conhecimento Em Projeto Automotivo: O Ecosport Da Ford Do Brasil

Abstract: A experiência de uma das equipes de desenvolvimento do projeto do novo EcoSport na Ford Motor Camaçari /BA foi investigada quanto ao compartilhamento de conhecimento entre os seus membros. O objetivo era avaliar aquela experiência, com vistas ao aprimoramento de futuros trabalhos. O foco da investigação foi posicionado em duas questões: a) Como o conhecimento foi compartilhado? e b) Qual a efetividade do compartilhamento de conhecimento? Para obter respostas a essas perguntas, foi realizada uma pesquisa entre … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
2
1
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 17 publications
0
2
1
2
Order By: Relevance
“…That is, it was found that socialization does not influence innovative behavior in a statistically significant, direct, or positive way. Contrary to the results obtained in this study, Sampaio et al (2014) found that socialization was the mode of transmission of knowledge to which the project development team attributed greater importance and that socialization is the preferred mode of knowledge capture. Similarly, Junior and Yu (2017), when studying the transformation of organizational knowledge based on the innovation process, found that in a pre-development phase, socialization stands out, revealing a greater intensity of tacit knowledge.…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…That is, it was found that socialization does not influence innovative behavior in a statistically significant, direct, or positive way. Contrary to the results obtained in this study, Sampaio et al (2014) found that socialization was the mode of transmission of knowledge to which the project development team attributed greater importance and that socialization is the preferred mode of knowledge capture. Similarly, Junior and Yu (2017), when studying the transformation of organizational knowledge based on the innovation process, found that in a pre-development phase, socialization stands out, revealing a greater intensity of tacit knowledge.…”
Section: Discussioncontrasting
confidence: 99%
“…Socialization translates into the conversion mode that can be seen as the starting point for the complete process of knowledge creation, characterized by the interaction between individuals, who communicate with each other without the need for codes or explicit forms for the message (Sampaio et al 2014). It is the process of sharing tacit knowledge or knowledge that is difficult to put into words, through interactions and experiences with other people.…”
Section: Explicit Knowledge Internalization Combinationmentioning
confidence: 99%
See 1 more Smart Citation
“…Conforme Raffaelli et al (2019), no âmbito interno, as decisões executivas se concentram na formação continuada e no aprimoramento da capacidade para inovar, aperfeiçoando intensamente suas habilidades para executar as atividades inovativas, estimulando a flexibilidade e a autonomia de suas equipes. Estes esforços têm sido reconhecidos como capazes de tornar as empresas mais capacitadas, melhor gabaritadas para reconfigurar seus recursos, implementar e gerenciar projetos de inovação, remodelar seus processos e otimizar seus investimentos (Sampaio et al, 2014). No quadrante externo, as diretrizes executivas também têm sido refinadas, principalmente para as empresas que enfrentam ambientes dinâmicos, competitivos e, igualmente, instáveis (Raffaelli et al, 2019).…”
Section: Ambidesteridade E Inovaçãounclassified
“…No desenvolvimento de produtos complexos, demanda-se um maior entendimento dos fluxos de conhecimentos para gerenciar o ambiente de projeto, disseminando-o, expandindo-o e utilizando-o eficazmente, com vistas a projetos cada vez melhores (Sampaio, Passos e Assis, 2014). Ainda no contexto de definição de um projeto de produto, Silveira et al (2018) citam que o pdp pode ser considerado um conjunto de atividades que têm início na percepção de uma oportunidade de mercado e têm como resultado a produção e comercialização de um produto.…”
Section: Marketingunclassified